Anticariogenic Activity and Haemolytic Study of Some Medicinal Plants Leaf Protein Extract against Six Oral pathogens in In vitro condition - Soni, Hiral; Ishnava, Kalpesh; Patel, Khushal (International Journal of Applied Sciences and Biotechnology, 2014)
<!–[if gte mso 9]> <![endif]–> Leaf extract of 12 medicinal plants were obtained by using 10mM sodium phosphate buffer and studied for their antibacterial activity against 6 cariogenic pathogens. Among them, the extract from Streblus asper showed the most intensive activity. Antibacterial activity of Streblus asper was investigated by the minimum inhibitory concentration (MIC) test and the viable cell count method. MIC of Streblus asper against Candida albicans causing dental caries was determined to be 2.5 μg/ml. The kinetic study showed that Streblus asper completely inactivated C. albicans at the concentration 50μg/ml in 15hours.Hemolytic study of the Streblus asper plant leaf protein gives HC50 value at a very high range than that of the MIC values against C. albicans of the organisms and thus flourish its application as successful pharmaceutical drug in practice. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.9344 Int J Appl Sci Biotechnol, Vol. 2(3): 253-259 <!–[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>